Personal Protective Equipment Reference Guide for Low-Volume Ground Citrus Applicators - Steve H. Futch; Lukasz L. Stelinski; Michael E. Rogers; Jamie D. Yates (EDIS)
This revised 2-page fact sheet provides a table describing personal protective equipment requirements for several products used in citrus production. Written by S.H. Futch, L.L. Stelinski, M.E. Rogers, and J.D. Yates, and published by the UF Department of Horticultural Sciences, July 2011.